MicroRNA-425-5p Inhibits Lung Cancer Cell Growth and by Downregulating TFIIB-Related Factor 2 - Xi Yu MD; Hong Zheng MD; Rongfei Sun PhD; Xuejiao Qian MD; Ping Jiang PhD; Bo Yang MD; Jiangbo Liu MD; Xiaoping Li MD (Technology in Cancer Research & Treatment, 2020)
Lung cancer is the most common cancer type with increasingly high incidence. MicroRNAs provide the potential biomarkers for lung cancer treatment. Thus, we aimed to investigate the function of microRNA-425-5p in lung cancer development and the underlying mechanisms. MicroRNA-425-5p overexpression inhibited A549 lung cancer cell proliferation in vitro and in vivo . On the other hand, microRNA-425-5p inhibition increased A549 proliferation. Mechanistically, the underlying mechanism by which microRNA-425-5p inhibits lung cancer cell growth was mediated through its ability in targeting and downregulating the TFIIB-related factor 2. Our results for the first time identified microRNA-425-5p as a tumor suppressor in lung cancer. Thus, microRNA-425-5p may serve as a potential therapeutic target for lung cancer.